Influence of usage of e-books, online educational materials, and other programming books and students' profiles on adoption of printed programming textbooks. Issue 4 (7th November 2017) - Bringula, Rex Perez
Abstract : Purpose: The purpose of this paper is to determine the influence of students' profiles and the usage of e-books, online educational materials, and other programming books on the adoption of printed programming textbooks for computing students. It was hypothesized that the predictor variable set could not explain any of the variance of the dependent variables. Design/methodology/approach: This descriptive study utilized a content-validated questionnaire. The study involved 190 student participants. Canonical correlation analysis was employed to determine whether students' profiles and use, perceived usefulness, and preference of e-books, online educational materials, and other programming books explained any variance in printed programming textbook adoption. Findings: Printed programming textbook adoption could be explained by two functions. The first function revealed that the use and the perceived usefulness of textbooks were positively influenced by the use of e-books and other programming books and by the perceived usefulness of e-books, fora/blogs, other programming books, and YouTube. The second function revealed that the use of printed programming textbooks alone was positively influenced by the use of e-books and other programming books but was negatively influenced by the perceived usefulness of programming websites and YouTube and by the preference of programming websites over textbooks. Originality/value: The study provided empirical evidence that e-books, other programming books, and online educational materials provide additional resources to students. Thus, e-books, online educational materials, and other programming books complement, rather than threaten, the existence of printed programming textbooks.